Reducing internet demand-side gap improves digital inclusion in low-income countries: - analysis that is more comprehensive - Mekuria Haile Teklemariam; Youngsun Kwon (International Telecommunications Society (ITS), 2018)
Reducing the broadband demand-side gap brings greater improvement in digital inclusion especially in low-income countries compared to developed economies. The demand-side gap between network coverage and penetration is less than 10% in developed countries. However, the digital divide and demand-side gap in low-income countries reach 60% and 30% respectively. From this, we developed the hypothesis: the effective use of existing internet facilities can reduce half of the digital divide in low-income countries. To test this hypothesis using regression analysis, we collected four-year data of 120 economies with 44 factors. The present study findings show that 100 points change in policy and regulation of ICT, energy infrastructure, gender literacy, software piracy rate, demographic dividend, competition in telecom sector, network coverage and quality, digital content, digital skill, and gender income will bring 5.5, 10, 6, -15.8, 12, 12.5, 12, 12.5, 24.4, 13, 15, and 8.5 points change in the internet usage of individuals respectively. Furthermore, 100 points change in this internet usage of the individuals will also bring 51.9 points increase on use of the existing network facilities. This implies that low-income countries can improve their total internet subscription significantly by increasing the internet usage of individuals without having further investment. Therefore, low-income countries can use these findings as input for their digital inclusion policy that shows how to improve the driving factors and internet subscription of their citizens.
Keywords: 330; Demand-side gap; low-income countries; digital skill; internet usage of individual; infrastructure access